SISTEM PENDUKUNG KEPUTUSAN PENENTUAN LOKASI LAHAN PERTANIAN UNTUK BUDIDAYA TANAMAN JERUK KEPROK MENGGUNAKAN FUZZY MULTI ATRIBUTE DECISSION MAKING (FMADM) DAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Leonardus Naben; Kornelis Letelay; Emerensye Sofia Yublina Pandie (J-Icon : Jurnal Komputer dan Informatika, 2020)
In commodity, oranges is one fruits that have benefit to be organized. The agribusiness of orange could increase farmers’ prosperity if it organized wholeheartedly. Besides, it is not only expand thereigional economic matters but also increasing the national emolument. Nowadays, the determining area of cultivation of oranges in TTS regency still did in manual way. occasionally, the farmers constrain the land utilizing of citrus fruit. The exposure of the land in the inappropriate area can lead the costs to be more expensive than the percentage agricultural commodities in the future. The Agriculture Department still estabish the location manually, so the information of decission support system of ariculture area is less accurate. That is why the use of FMADM decission support system and SAW method very precise to implement in this case. This research use 7 criteria rain, temperature, drainae, pH H2O, texture of land, and slope. The comparing of manual computation and system computation by examination system. The results are same but the outcome of the system is better than manually. In measuring the importance of weight use sensititifity examine of weight repair with 10 data location that found by the researcher in BPTP East Nusa Tenggara. The result found the more sensitive criteria is slope which has sensitive levels 60%. Finally, after the system result add 0.5 and 1, show contrast result of rank of the data. The data analyze found the system extend better result.